THE USE OF NAFTIFINI HYDROCHLORIDE AND ITS ADVANTAGES IN THE TREATMENT OF VARIOUS TYPERS OF FUNGAL DISEASES - S. I. Kosenkova; I. I. Krasnyuk; I. I. Krasnyuk (Jr.) (Разработка и регистрация лекарственных средств)
Studying the susceptibility of dermatophyte strains to naftifine revealed that the range of inhibitory concentrations (MIC) is 0,1-0,2 μg/ml. The naftifine spectrum is very wide and includes almost all mycotic pathogens. Testing the strains of Trichophyton rubrum, Trichophyton mentagrophytes, Microsporum canis and Epidermophyton floccosum in comparison with clotrimazole and 4-imidazole antimycotics has shown that naftifine is the most active drug affecting dermatophytes. In concentrations of no more than 1,0 μg/ml, naftifine inhibited 98,75% of dermatophyte strains. Naftifine hydrochloride can find a worthy use in the treatment of skin diseases against the background of infectious and inflammatory processes associated with mycoses.